Real-world Experience of Rituximab in Immune Thrombocytopenia - Mishra, Kundan (Indian J Hematol Blood Transfus, 2021)
Immune thrombocytopenia (ITP) is a relapsing–remitting disease often requiring more than one line of therapy. Rituximab is a recommended second-line therapy, but the real-world data on its efficacy and safety from resource constraint settings is limited. We aimed to analyze the safety and efficacy of rituximab in ITP. This is a single-center, retrospective study. This study was conducted at a tertiary care hospital in Northern India from 2005 to 2019. On audit of medical records, all patients of ITP (n-513) who had received rituximab (n-81) were screened for inclusion. Patients whose response assessment was not possible were excluded. Finally, 66 patients were analyzed using statistical packages of Python v3.7. The cumulative incidence of overall response on day 20 was 30.61%, and day 30 was 51.72%. The median time to response was 28 day (range 21–51 day). Cumulative incidence of complete response was 16.67%, and partial response 37.88%. After a median follow-up of 789 day (range 181–5260 day), the cumulative incidence of relapse was 30.32%, 36.12%, and 56.57% at 1, 2, and 5 years respectively. There was no effect of age, sex, duration of disease, lines of therapy received, and platelet count on either cumulative incidence of overall response or relapse. ANA positivity was significantly related to the better cumulative incidence of overall response (p = 0.012), but not with relapse. Infusion-related reactions were the commonest adverse event noted (n-4, grade ≥ 3 CTCAEv4). Rituximab and its generic version are safe and effective second line agent in ITP with a good overall response and sustained response.